On Designing Event-Triggered Schemes for Networked Control Systems Subject to One-Step Packet Dropout - Wu, Di; Sun, Xi-Ming; Tan, Ying; Wang, Wei (IEEE transactions on industrial informatics, 2016)
Different from time-triggered control strategies, the event-triggered control (ETC) scheme takes action (e.g., sensing and actuation) when needed, which will greatly reduce the communication traffic in networked control systems (NCSs). On the other hand, due to reduced number of transmissions, the ETC is more vulnerable to communication dropouts compared with the periodic sampling. This paper focuses on a special Lyapunov-based ETC design with the consideration of packet dropouts. The closed-loop system with the ETC and packet dropouts can be rewritten as a switched system, switching between the normal transmission and the communication dropout. By adapting the well-known concept, average dwell-time in switched systems, the main result of this paper provides sufficient conditions in terms of transmission intervals that can ensure the closed-loop stability in the presence of transmission dropouts. Experimental results using dc-motor-based speed control have demonstrated the effectiveness of the proposed method.